2023
DOI: 10.1002/adem.202201063
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineering Bone‐on‐a‐Chip Model Harnessing Osteoblastic and Osteoclastic Resolution

Abstract: Organ-on-a-chip (OoC) systems allow the generation of microphysiological tissue models that can recapitulate key biological processes in healthy and diseased states. OoC bone models provide valuable tools to study crosscellular interactions that take place in bone-related processes. Although few bone-on-a-chip models have been proposed, structural and biological hierarchy to establish a functional unit is often lacking. Herein, a functional OoC-based 3D bone co-culture model is reported. This model comprises a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Alternatively, one of the materials suggested to make ceramic scaffolds is β-tricalcium-phosphate (β-TCP) due to their ability to fabricate porous scaffolds allowing for the development of a dense ECM that is required for bone remodelling [10]. Erbay et al (2023) proposed a 3dimensional bone co-culture where primary osteoblast and F4/F80 + osteoclast precursors were seeded in the TCP base scaffold and cultured in a microfluidic setup for up to 21 days. A polymer foam replication method was used to make the scaffold and the TCP powder was grinded down to control the geometry of the scaffold.…”
Section: Scaffolds Of Bone-on-a-chip Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…Alternatively, one of the materials suggested to make ceramic scaffolds is β-tricalcium-phosphate (β-TCP) due to their ability to fabricate porous scaffolds allowing for the development of a dense ECM that is required for bone remodelling [10]. Erbay et al (2023) proposed a 3dimensional bone co-culture where primary osteoblast and F4/F80 + osteoclast precursors were seeded in the TCP base scaffold and cultured in a microfluidic setup for up to 21 days. A polymer foam replication method was used to make the scaffold and the TCP powder was grinded down to control the geometry of the scaffold.…”
Section: Scaffolds Of Bone-on-a-chip Modelsmentioning
confidence: 99%
“…A polymer foam replication method was used to make the scaffold and the TCP powder was grinded down to control the geometry of the scaffold. X-ray diffraction (XRD) analysis was able to show that the scaffold was able to retain osteogenic properties and SEM was able to show that macropore sizes ranged from 500 to 50 μm, while micropore sizes ranged from 10 to 1 μm indicating that the scaffold is very porous [15]. Computational fluid dynamic simulations were able characterize the flow pattern in the bone-on-a-chip model which showed that the flow velocity was slower near the boundaries of the channels than in the corner [15].…”
Section: Scaffolds Of Bone-on-a-chip Modelsmentioning
confidence: 99%
See 3 more Smart Citations